Governance, Peace and Security in Sub-Saharan Africa : Microeconomic interaction and impacts - (:unkn) unknown (My University, 2020)
This dissertation in applied development microeconomics centres on Sustainable Development Goal 16 which “promote[s] just, peaceful and inclusive societies”. This work aims at studying the interactions and effects of Governance, Peace and Security through the analysis of first-hand and high-quality household survey data in SubSaharan Africa. It is built around two lines of research. The first line of research is cross-cutting and methodological: it questions the reliability of the data used. Indeed, public organisations, namely National Statistics Offices, administer the surveys and collect information of sensitive nature (dealing with respect of fundamental rights, democracy, corruption among other things). Results show no systematic self-censorship or attenuation bias from adults surveyed by NSOs compared with adults surveyed by independent organisations. We provide evidence of the capacity and legitimacy of government-related organisations to collect data on governance, at much higher levels of precision than other existing data sources. The second line of research focuses on the impacts of violence in two African countries. On the one hand, we study the impacts of political violence on social capital since 2012 in the case of the Malian conflict. The increased association participation in areas exposed to violent events cannot be considered as positive. Indeed, it is observed solely for family and political associations, which are comparatively inward-looking and act as interest groups. We interpret this finding as a form of withdrawal behind group or community boundaries which may exacerbate ethnic divisions and deepen the conflict. On the other hand, I study how workers of the informal labour market cope with criminal violence in Madagascar. Although victims of criminality seem not to adopt different behaviours on the labour market, the fear of crime impact productivity negatively, particularly in the agricultural sector. Fearful workers beco
Keywords: African Research